2019
DOI: 10.1080/10872981.2019.1690846
|View full text |Cite
|
Sign up to set email alerts
|

Ending student mistreatment: early successes and continuing challenges

Abstract: Problem: Student mistreatment represents an ongoing challenge for US medical schools. Students experiencing mistreatment may become marginalized and cynical, and they have higher rates of burnout, depression and substance use disorders. Although numerous attempts to eliminate mistreatment have been proposed, best practices remain elusive. We formed a unique student-faculty collaboration (the Ending Mistreatment Task Force) that allowed all voices to be heard and enabled identification of five interventions to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 42 publications
0
35
0
Order By: Relevance
“…One of its manifestations is to demand over-dimensioned academic tasks that surpass the student’s available resources and its formation-level [ 35 , 54 , 55 ]. These sources of mistreatment generate stress [ 56 , 57 ] and affect the well-being of the student [ 58 , 59 ]. This is especially complex in a context where the students lack certainties about how the formation processes will continue and at what time they will be able to complete them [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of its manifestations is to demand over-dimensioned academic tasks that surpass the student’s available resources and its formation-level [ 35 , 54 , 55 ]. These sources of mistreatment generate stress [ 56 , 57 ] and affect the well-being of the student [ 58 , 59 ]. This is especially complex in a context where the students lack certainties about how the formation processes will continue and at what time they will be able to complete them [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 49 unique studies, 10 implemented organisationlevel interventions which included workshops with vignettes to improve recognition of bullying (reported in 4 studies) 23 37 42 44 ; a gender and power abuse committee that established reporting mechanisms and held mandatory workshops on mistreatment (reported in 1) 3 ; a gender equity office to handle reporting (reported in 1) 39 ; a professionalism-focused approach that included professionalism in employee contracts and performance reviews, and a professionalism office to handle student complaints (reported in 1) 26 ; zero-tolerance policies (reported in 1) 53 and institutional-level tracking of mistreatment to provide targeted staff education (reported in 2). 21 24 All 10 studies had an uncontrolled before-after design, and as such, did not establish causality.…”
Section: Suggested Strategies Interventions and Outcomesmentioning
confidence: 99%
“…3 Similarly, in a study that used a multifaceted approach of developing a professionalism committee, and including professionalism in contracts and performance reviews, there was a 35.9% decrease in reporting of mistreatment and improved awareness of the reporting process. 26 In a study where a clerkship committee monitored unprofessionalism, there was an associated reduction in narrative comments regarding unprofessionalism on end of rotation surveys. 21 In a study assessing the impact of a professionalism retreat about mistreatment for consultants, there was no reduction in medical student mistreatment.…”
Section: Suggested Strategies Interventions and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although mistreatment remains a challenging issue in medical education, problems are preventable with appropriate communication and a clear understanding between medical personnel and students [ 33 , 35 , 39 ]. However, several studies have shown that managing systems to eliminate such problems remains ineffective and unsafe [ 28 , 32 ].…”
Section: Introductionmentioning
confidence: 99%